Simulasi kendali sistem pendulum terbalik menggunakan metoda Fuzzy dan konvensional=Simulation of the inverted pendulum system and control using fuzzy and conventional method - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
The inverted pendulum system represents a challenging control problem, where the system can continually move toward an unstable state. This problem has been studied and has been simulated using MATLAB programming language. The main objective of this simulation is to build models of fuzzy and conventional controllers that can be used in keeping a pole (pendulum) in vertical position while the cart is moving. The performances of the fuzzy and conventional controllers are compared to see the response of these controller. The conventional controller is represented via state feedback, whereas fuzzy controller developed here is implemented using SIMULINK. The simulation results show that both fuzzy and conventional controller can be used to stabilize and to control the inverted pendulum system. The fuzzy controller system shows greater improvement over conventional controller, especially it gives less overshoot, few oscilation around set point, and shorter settling time.